Microstructure of Oxide Dispersion Strengthened Steel With Cr Content Variation - Marzuki Silalahi; Bernadus Bandriyana; Arbi Dimyati; Bambang Sugeng; Syahfandi Ahda; Fitria N (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
Microstructure and phase distribution of innovative Oxide Dispersion Strengthened (ODS) steel based on Fe-Cr-ZrO2 particularly for application at high temperature reactor with variation of Cr content was analysed. The alloy was synthesized with Cr composition variation of 15, 20 and 25 wt.% Cr, while zirconia dispersoid kept constant at 0.50 wt.%. The samples was synthesized by mechanical alloying comprising of high energy milling for 3 hours followed by vibrated compression with iso-static load at 20 ton. The final consolidation was performed via sintering process for 4 minutes using the Arc Plasma Sintering (APS) technique, a new method developed in BATAN especially for synthesizing high temperature materials. The samples were then characterized by means of scanning electron microscopy (SEM) with energy dispersed X-ray (EDX) analysis capability and X-ray diffraction. The mechanical property of hardness was measured using standard Vickers micro hardness tester to confirmed the microstructure analysis. The results show that the microstructure of the ODS alloy samples in all variation of Cr content consists generally of cubic Fe-Cr matrix phase with small of porosity and Zirconia particles distributed homogenously in and around the matrix grains. The achievable hardness was between 142 and 184 HVN dependent consistently on Cr content in which Cr element may cause grain refining that in turn increase the hardness.